BREEDING HABITATS AND INSECTICIDE SUSCEPTIBILITY OF Anopheles gambiae AND Culex Quinquefasciatus IN ILORIN, NIGERIA - Olukayode, James Adelaja; Tosin, Awodoyin; Aker, Palegh; Ayoola, Emmanuel Abiola; Hassanat, Ore; Adeolu, Taiwo Ande (FUDMA JOURNAL OF SCIENCES, 2026)
Urban mosquito breeding habitats and insecticide resistance pose major public health challenges in Nigeria. This study characterised larval habitats and insecticide susceptibility of Anopheles gambiae and Culex quinquefasciatus in Ilorin. Larvae were collected from ten sites during the 2011 rainy season, and habitats were profiled by water physicochemical properties (temperature, pH, conductivity, total dissolved solids, heavy metals) and vegetation. Adult susceptibility was tested against five WHO-recommended insecticides. An. gambiae predominated in sunlit, turbid, polluted waters with submerged vegetation; Cx. quinquefasciatus occurred in both sunlit and shaded habitats. Propoxur gave the highest mortality: 80.3% in An. gambiae and 94.1% in Cx. quinquefasciatus. Primiphos methyl was least effective, killing only 4.9% of An. gambiae. Pyrethroids showed moderate efficacy (60–75%). Principal component analysis revealed strong correlations of iron and manganese with polluted sites, indicating heavy metal contamination. These pre-long-lasting insecticidal net baseline data expose alarming resistance to DDT and organophosphates and underline the urgent need for integrated vector management, insecticide rotation, larval habitat modification, and continuous resistance monitoring.